Optimization Of The Development Of Social Emotional Learning (SEL) Tools In Supporting Independent Learning For Teachers Of Central Java MGMP Economics - Widodo, Joko; Murniaty, Indri; Sehabuddin, Ahmad; Listiyani, Ajeng; Rohmah, Ira Nur (Indonesian Journal of Devotion and Empowerment, 2024)
Implementing an independent curriculum will be able to realize the rights and abilities of participants to determine their learning process through setting learning goals, reflecting on abilities, and taking steps proactively and responsibly for their own success. The problems in the free learning curriculum are teachers who use learning techniques that are not appropriate to the conditions or circumstances, lack of use of learning media, and monotonous teaching. The reality in the Economic MGMP of Central Java Province is that the development of social emotional learning (SEL) learning tools based on the independent learning curriculum and its development is still very diverse regarding tools that have not been developed based on the independent learning curriculum. The aim of this service is to increase teachers' understanding and skills in designing learning tools in the form of lesson plans, materials and evaluation instruments. The methods used in service include outreach activities, training, mentoring and evaluation of service programs. The results of the service are a) increasing understanding of the concept of social emotional learning for Central Java Economics MGMP teachers; b) able to implement social emotional learning in learning tools to support the independent learning curriculum.